Antiferroelectric to relaxor ferroelectric phase transition in PbO modified (Pb0.97La0.02)(Zr0.95Ti0.05)O3 ceramics with a large energy-density for dielectric energy storage. Issue 68 (7th September 2017) - Li, Bi; Liu, Qiu-Xiang; Tang, Xin-Gui; Zhang, Tian-Fu; Jiang, Yan-Ping; Li, Wen-Hua; Luo, Jie
Abstract : The recoverable energy density and energy efficiency of the high energy density electrification PLZT2/95/5 ceramic capacitors as a function of the temperature and electric field. Abstract : (Pb0.97(1+ x ) La0.02 )(Zr0.95 Ti0.05 )O3 (PLZT2/95/5) ceramics with excess lead content ( x = 0, 3%, 5%, 7.5%, 10% and 15%) were successfully prepared via a solid-state reaction route. X-ray diffraction analysis indicated that a pure perovskite structure was obtained for all compositions. The effects of excess lead content on the microstructure, dielectric properties, and energy-storage performance of PLZT2/95/5 ceramics were systematically investigated. The ceramics exhibited tetragonal phase structures and showed two dielectric peaks at 120 and 240 °C, corresponding to antiferroelectric–ferroelectric and ferroelectric–paraelectric phase transitions. The recoverable energy-storage density calculated from hysteresis loops reached about 2.12 J cm −3 with an efficiency of 92.98%, which was due to the phase transition from the antiferroelectric state to the relaxor ferroelectric state. Based on these results, typical PLZT2/95/5 ceramics with different lead excess content have been studied, which could be potential candidates for applications in high energy storage-density electrical capacitors.